2009
DOI: 10.1292/jvms.71.171
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous Embolism of the Spinal Cord Diagnosed by Characteristic Clinical Findings and Magnetic Resonance Imaging in 26 Dogs

Abstract: ABSTRACT. Fibrocartilaginous embolism (FCE) is a disorder of acute onset that presents with nonprogressive ataxia. We performed a retrospective examination of FCE of the spinal cord diagnosed by characteristic clinical findings and magnetic resonance imaging (MRI) in 26 dogs. In the present study, treatment consisting of physiotherapy alone, or this in combination with corticosteroid administration, was initiated immediately following diagnosis of FCE. Age at onset and the gender ratio in the present study clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 19 publications
4
42
0
3
Order By: Relevance
“…Myelography is used for excluding compressive myelopathies and offers the additional advantage of cerebrospinal fluid collection for analysis. Patients with fibrocartilaginous embolic myelopathy may show an intramedullary pattern, associated with spinal cord swelling around the embolised region, or have normal findings in myelography (Nakamoto et al, 2008;Nakamoto et al, 2009). In this study, myelogra phy was performed in all cases and indicated no spinal cord compression.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Myelography is used for excluding compressive myelopathies and offers the additional advantage of cerebrospinal fluid collection for analysis. Patients with fibrocartilaginous embolic myelopathy may show an intramedullary pattern, associated with spinal cord swelling around the embolised region, or have normal findings in myelography (Nakamoto et al, 2008;Nakamoto et al, 2009). In this study, myelogra phy was performed in all cases and indicated no spinal cord compression.…”
Section: Discussionmentioning
confidence: 73%
“…Although the large and giant breeds of dogs still represent a signifi cant proportion of animals reported in many relevant publications (Gandini et al, 2003), smaller breeds, as well as mixed breed dogs, may also be affected (Nakamoto et al, 2008, De Risio andPlatt, 2010), in some studies even outnumbering larger size animals (Nakamoto et al, 2008, Nakamoto et al, 2009). In the present study, six dogs were of large breed, whilst four were medium-and four small-sized dogs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, o diagnóstico definitivo e o mais preciso é o exame histológico post mortem com coleta do segmento da lesão medular e posterior coloração e análise microscópica (Nakamoto et al, 2009, De Risio and Platt, 2010, Mateen et al, 2011, Chaves et al, 2013, AbdelRazek et al, 2016, De Risio, 2015, Garavito-Bernal and León-Torres, 2015, Chaves et al, 2016.…”
Section: Discussionunclassified
“…Neste caso o laudo médico sugere diagnóstico compatível com EFC, devido à lesão de isquemia medular em região C6 que apresentava região de hipodensidade na mesma área, mas que o diagnóstico definitivo só poderia ser feito por meio da ressonância magnética. Embora a TC não seja o método mais preciso de diagnóstico, ela exclui algumas mielopatias de compressão medular, como a extrusão do disco cervical e traumas (Nakamoto et al, 2009, De Risio and Platt, 2010, Mateen et al, 2011, Chaves et al, 2013, AbdelRazek et al, 2016, De Risio, 2015, Garavito-Bernal and León-Torres, 2015, Chaves et al, 2016. Haja vista que o animal realizou o exame na fase aguda, onde este é mais PUBVET v.11, n.12, p.1220-1226, Dez., 2017 sensível e a região de hipodensidade indica fortemente a presença de edema na região, compatível com as lesões encontradas em TC com EFC (De Risio and Platt, 2010, Mateen et al, 2011, De Risio, 2015, Garavito-Bernal and León-Torres, 2015, De Risio, 2014.…”
Section: Discussionunclassified